EUPHEMISMS IN THE POLITICAL DISCOURSE OF AMERICAN AND BRITISH POLITICIANS - Амирова, Е.Л. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2015)
The definition of the concept "euphemism" is presented in the article, the functions of euphemisms and their types are described. The comparative analysis of peculiarities of use of euphemisms is carried out in B. Obama and T. Blair's speeches. Regularities of a political discourse in the speech of politicians of the USA and Great Britain are marked out.
Keywords: discourse; political discourse; euphemisms; peculiarities of euphemisms